Analysis of Product Design Long Leg Braces With Kansei Words Approach and Biomechanics - Sugiono sugiono; Bellyn Mey Cendy; Dewi Hardiningtyas (Indonesian Journal of Disability Studies, 2015)
Many aspects become consideration related to the needs and desires of consumers with disabilities. Categories of persons with disabilities using using the lame use walking aids (long leg braces) for everyday mobility. Long leg braces that are now in the market have some complaints. Incompatibility use walking aids prove that the identification and analysis of existing of long leg braces as consideration for further improvement. When using the product, 40 of long leg braces become the sample from 64 populations in Malang. The consumer of long leg braces tend to express a desire using abstract words. Identification of the feelings and emotions of the users done using kansei words. Kansei words represent human psychological as feelings and emotions. Considerations that appear on kansei words, become consideration in the calculation of biomechanics. Therefore,it is expected that the design of the new long leg braces are able to distribute energy/ the load of the user so it can reduce complaints based on kansei words. Based on the kansei questionnaire there are 25 pairs of words that represent the desire of consumers to the product. 7 factors which produce ergonomic consideration factors have the most variable. Adjustments to the forces and moments between the segments of the normal foot greatest force in doubled phase support pelvic segment amounted to 28.93 N and moment of inertia of 658.53 KgM2. With a recommendation on long leg braces segment so that the resulting mass at the base of the thigh segment amounted to 0.864 kg, 0.792 kg calf and the foot segment amounted to 0.182 kg. Biomechanical calculations have proved that complaints of long leg braces have the highest number of complaints on the suitability of the thigh segment based on kansei words.